2017
DOI: 10.3390/e19070342
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Feature Extraction Method for Ship-Radiated Noise Based on Variational Mode Decomposition and Multi-Scale Permutation Entropy

Abstract: Abstract:In view of the problem that the features of ship-radiated noise are difficult to extract and inaccurate, a novel method based on variational mode decomposition (VMD), multi-scale permutation entropy (MPE) and a support vector machine (SVM) is proposed to extract the features of ship-radiated noise. In order to eliminate mode mixing and extract the complexity of the intrinsic mode function (IMF) accurately, VMD is employed to decompose the three types of ship-radiated noise instead of Empirical Mode De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…(1) Select the low-frequency IMF for the research, such as the last IMF; (2) Obtain estimated frequency of selected IMF by VMD; (3) Detect periodic signal of selected IMF using DCO; (4) When the phase track of selected IMF is in great periodic, and the KPE of DCO system output reaches the maximum, we can determine the accurate frequency of selected IMF.…”
Section: Frequency Feature Extraction Methods For Underwater Acoustic mentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Select the low-frequency IMF for the research, such as the last IMF; (2) Obtain estimated frequency of selected IMF by VMD; (3) Detect periodic signal of selected IMF using DCO; (4) When the phase track of selected IMF is in great periodic, and the KPE of DCO system output reaches the maximum, we can determine the accurate frequency of selected IMF.…”
Section: Frequency Feature Extraction Methods For Underwater Acoustic mentioning
confidence: 99%
“…Underwater acoustic signal processing is one of the hot topics in the field of marine science. The denoising, feature extraction and classification of underwater acoustic signals are of great significance to the research of underwater acoustic signals, which can provide convenience and basis for the detection and tracking of underwater acoustic signals [1][2][3][4]. Feature extraction methods for underwater acoustic signals mainly include frequency feature extraction, energy feature extraction and complexity feature extraction [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [29], an improved decomposition method, VMD and PE are used for fault extraction. In [30], VMD, Multi-Scale Permutation Entropy (MPE) and Support Vector Machine (SVM) were used to extract the characteristics of underwater acoustic signals. The study found that although the above method continuously improves the signal decomposition effect, it does not solve the problem that PE may lose amplitude information.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the mode mixing of EMD, ensemble EMD [11] was put forward after EMD, which inhibits this phenomenon to some extent by adding noise. Still, EEMD and other improved EMD methods are all empirical ones without mathematical derivation [12]. In recent years, the two kinds of data-driven decomposition methods have developed rapidly.…”
Section: Introductionmentioning
confidence: 99%